2007
DOI: 10.1007/s00204-007-0266-6
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral impairments related to lead-induced developmental neurotoxicity in chicks

Abstract: Lead intoxication affects the central nervous system and produces structural disorders and behavioral deficits in several animal species. Although lead neurotoxicity is a well-reported phenomenon, studies on the developmental neurotoxicity induced by this metal in avian are scarce. The aim of this study was to evaluate how a single dose of 28 mug lead acetate administered into the yolk sac on the fifth incubation day of Gallus domesticus can affect the behavior and the brain tissue in the first postnatal week.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…Previous studies have shown that lead exposure could decrease activity levels in animals [58,59]. The present study established decreased locomotor activities in lead exposure rats as evidenced by lower numbers of rearings and crossings.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies have shown that lead exposure could decrease activity levels in animals [58,59]. The present study established decreased locomotor activities in lead exposure rats as evidenced by lower numbers of rearings and crossings.…”
Section: Discussionsupporting
confidence: 77%
“…In the laboratory, the eggs were placed in an incubator in a horizontal position at 37.5-38.0°C and 65.0% humidity (Müller et al 2008). All experiments were carried out according to the guidelines of our institution's Ethics Committee (CEUA-UFSC), project number 23080.032216/ 2005-18/UFSC.…”
Section: Eggs and Embryosmentioning
confidence: 99%
“…Young animals are known to be more sensitive to detrimental effects of Pb and other pollutants than adults for example due to their underdeveloped digestion, and especially underdeveloped blood-brain barrier (Burger and Gochfeld 2000;Dietert and Piepenbrink 2006;Domingo 1994;Scheuhammer 1987). In the central nervous system, Pb disturbs synaptic and receptor functions and impairs synaptic growth (Bressler and Goldstein 1991;Gilbert et al 2005; for birds, see: Muller et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However birds, especially in the wild, are little studied. The few existing studies in birds document multiple negative effects of early-life Pb exposure on behavior (both instant and delayed): in gulls, ducks, and chickens, Pb and other metals impaired balance and movement (Burger and Gochfeld 1995a;Douglas-Stroebel et al 2005;Muller et al 2008), begging and feeding behavior Gochfeld 1994, 2005), caused behavioral changes in thermoregulation (Bouton et al 1999;Gochfeld 1985, 1995b), and impaired individual recognition (Burger 1998;Burger and Gochfeld 1993). Developmental Pb exposure has been found to impair learning and memory in some tasks (Burger and Gochfeld 2005;Zhong et al 2010).…”
Section: Introductionmentioning
confidence: 99%